An examination of the possibilities and issues in the rural market - HIMANSHU KARGETI (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Because of its scope and large customer base, the Indian rural sector presents both domestic and international advertisers with numerous chances. Agriculture and the rural market are also, directly and indirectly, important to the Indian economy. Due to the overall expansion of the Indian economy and the consequent rise in the buying power of rural Indian households, rural marketplaces in India have recently assumed a significant role. The green movement and better infrastructure for rural residents are further reasons why a significant portion of industrialized and manufactured products are being consumed in rural areas. Marketing strategy has become a unique marketing method in this situation (Verma, 2013)